Modernity, Heritage and Identity: Interpretations of the Public Space in the City of Ibarra in the Digital Age - Torres, Jorge (2020)
Ibarra is a city in full development. Its foundation as a colonial city in 1606, in a valley already inhabited by important indigenous communities, with its subsequent but slow transition into a capitalist modernity, generated transformations and transitions on both ideological and material degrees. Thus, the city and its public space must be interpreted as a document or device, as the changes that have taken place convey a particular discourse. Ibarra sees itself as a localized city that mutates towards an emplaced society, which is shifting from its baroque and republican past towards a heterotopic present and future. This is a space that allows, by its own discursive logics, to create new spaces. This research aims to contribute with a new reading to the debates on Heritage and Identity in the digital era, and more importantly to establish distances in light of conservative or postmodernist discourses. Heritage is not a stationary space, nor is it Identity, and this is not just an antiquated narrative from a remote past. Both are devices that also in the Digital Age express goals and desires of a society. Information and Communication Technologies are a powerful device for the reproduction of these discourses, which are ultimately the spokespersons for structures of socio-cultural and socio-racial domination. The fact of living in this digital technological age does not make us immune to the resources and strategies of capitalist power, but more vulnerable to them.